Therapeutic potential of oxadiazole or furadiazole containing compounds - Siwach, Ankit (BMC Chem, 2020)
As we know that, Oxadiazole or furadi azole ring containing derivatives are an important class of heterocyclic compounds. A heterocyclic five-membered ring that possesses two carbons, one oxygen atom, two nitrogen atoms, and two double bonds is known as oxadiazole. They are derived from furan by the replacement of two methylene groups (= CH) with two nitrogen (-N =) atoms. The aromaticity was reduced with the replacement of these groups in the furan ring to such an extent that it shows conjugated diene character. Four different known isomers of oxadiazole were existed such as 1,2,4-oxadiazole, 1,2,3-oxadiazole, 1,2,5-oxadiazole & 1,3,4-oxadiazole. Among them, 1,3,4-oxadiazoles & 1,2,4-oxadiazoles are better known and more widely studied by the researchers due to their broad range of chemical and biological properties. 1,3,4-oxadiazoles have become important synthons in the development of new drugs. The derivatives of the oxadiazole nucleus (1,3,4-oxadiazoles) show various biological activities such as antibacterial, anti-mycobacterial, antitumor, anti-viral and antioxidant activity, etc. as reported in the literature. There are different examples of commercially available drugs which consist of 1,3,4-oxadiazole ring such as nitrofuran derivative (Furamizole) which has strong antibacterial activity, Raltegravir as an antiviral drug and Nesapidil drug is used in anti-arrhythmic therapy. This present review summarized some pharmacological activities and various kinds of synthetic routes for 2, 5-disubstituted 1,3,4-oxadiazole, and their derived products. [Image: see text]